Full Dollarization : The Pros and Cons - Borensztein, Eduardo; Berg, Andrew (Washington, D.C. : International Monetary Fund, 2001)
Analyzes the costs and benefits of full dollarization, or the adoption by one country of another country's currency. Potential advantages include lower borrowing costs and deeper integration into world markets. But countries lose the ability to devalue, and become dependent on the U.S. Compares with currency board option.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet